Anticipatory control of impending postural perturbation in elite springboard divers - Popa, T.; Bonifazi, M.; della Volpe, R.; Rossi, A.; Mazzocchio (European Journal of Applied Physiology, 2008)
Among athletes, elite springboard divers (ED) should develop an optimal anticipatory control of postural stability, as a result of specific training. Postural strategies of ED and healthy subjects (HS) while expecting an impending perturbation were compared. The mean center of pressure (COP) position was analyzed during control quiet stance (cQS) and during anticipatory quiet stance (aQS1-4), i.e., in expectation of four backward translations of the support surface. During cQS, COP position in ED was not significantly different as compared to HS. During aQS1-4, a significant increase in the mean COP position was observed in both groups with ED adopting a more forward inclined vertical alignment than HS. In ED specific training may have resulted in a reference frame offset in a more anterior direction while expecting an impending perturbation. We suggest that leaning more forward may represent a more reliable way of coping with predictable perturbations of postural stability.